Deterioration modelling of flexible pavements with modified bitumen in wearing course - Deori, Sanjay (My University, 2018)
India is developing its highway infrastructure through widening and rehabilitation of existing national highways under different phases of National Highway Development Program (NHDP). The NHDP road network is considered as a high speed road corridor of India. Use of modified bituminous binders have increased manifold in the last decade in India, mainly in the bituminous concrete (BC) hot mix asphalt wearing course of flexible pavements. Because of their enhanced engineering properties, modified binders are preferred to conventional (unmodified) binders. Crumb rubber-modified bitumen (CRMB) and polymer-modified bitumen (PMB) are the most common modified binders used with the intent to improve the pavement performance against large variations in temperatures and continually increasing axle loads on Indian roads.
Choudhary, Rajan
Tiwari, Devesh
Keywords: CIVIL ENGINEERING